The Stigma and stereotype notions of community towards the urban homeless at Komtar, Pulau Pinang, Malaysia - Abu Bakar, Mohd Azmeer; Nur Farhanah Husain; Nooriah Yusoff; Norhayati Mat Ghani (The Institute of Academic Research and Publication (IARP), 2024)
Homelessness is a pervasive issue that impacts both developed and developing nations, including Malaysia. This situation gives rise to multiple stigmas and misconceptions within the community. The problem of homelessness in Penang is a significant concern for government authorities and non-governmental groups, who are actively attempting to confront, mitigate, and assist in managing this situation. This study aims to ascertain the community's impression of people experiencing homelessness. The questionnaire survey included 387 respondents from the local community near Komtar, Pulau Pinang. A straightforward random selection was made using the participants' method. This study uses descriptive analysis and a relative importance index (RRI) to analyze the study data. The survey findings indicate a specific outlet or community categorization exists for those currently suffering homelessness, including those who do not have a permanent dwelling (homeless individuals (44.5%) and a significant fraction of wandering individuals (21.5%). Moreover, this study demonstrates that the perception of the homeless population is closely tied to their attire, which in turn is influenced by factors such as safety, surroundings, and location. This study on homelessness can offer significant insights to the Department of Local Government and Social Welfare regarding the community's view and response to homeless individuals in the area, which serves as an administrative centre. Moreover, this study can assist the Government in identifying the precise locations of homeless people. This would enable a more precise allocation of aid to the desired group, ultimately reducing the number of homeless individuals in Pulau Pinang.